ANALYSIS OF INFLUENCING FACTORS STREET VENDOR INCOME IN NEW SUB-DISTRICT BAOLAN TOLITOLI REGENCY (Case Study of Arang Tampurung Business) - Ismail, Ismail; Hairuddin, Hairuddin (STIE Mujahidin Tolitoli Development Economics Study Program, 2024)
This study aims to analyze the influence of business capital, working hours, business duration, and education level. The study is a quantitative research with primary data from the results of the questionnaire on a sample of street vendors in the New Village.The number of respondents to street vendors in the new Village is 53.The data from the questionnaire is processed using a linear probability model and processed using SPSS software. The results of the test were obtained on the variable